Mecanismos reguladores de SOCS2 no Sistema Nervoso Central, durante a Encefalomielite Autoimune Experimental - Allysson Thiago Cramer Soares (2017)
In recent years, Experimental Autoimmune Encephalomyelitis (EAE) has been the most widely used animal model to elucidate and better understand the pathophysiological mechanisms of Multiple Sclerosis (MS). A disease characterized in providing an inflammatory process exacerbated, generating a compromising and damaging The functioning of the Central Nervous System (CNS). Regulatory mechanisms of inflammation are extremely important to control the inflammatory profile during the development of the disease. It is known that proteins called Cytokine Signaling Suppressors (SOCS) have specific functions that regulate cytokine responses, counterbalancing the signaling and inflammatory process in several diseases. A member of the SOCS family, known as SOCS2, has been extensively studied in recent years, and has been classified not only as a suppressor, but as a modulator, because it presents diverse physiological responses in various body systems as well as in the pathogenesis of certain Infectious, allergic, cancerous and CNS-affecting diseases. However, little is known about the involvement of SOCS2 in autoimmune diseases, as well as the development of EAE. In order to study the role of SOCS2 in EAE, disease induction in C57BL / 6 and SOCS2 deficient mice ( - / - ) was performed using oligodendrocyte myelin (MOG35-55), Complete Freund's Adjuvant (CFA) and Pertussis toxin. After the development of the disease, analyzes of the brain and spinal cord were performed during the peak phase (14th day after induction - dpi) and in the remission phase (28 dpi) of the disease. Increased expression of SOCS2 in the brain of C57BL/6 mice during disease development was observed, whereas SOCS2-/- mice showed resistance to the appearance of acute phase clinical signs. This resistance was associated with reduced brain IRF1 expression, reduced inflammatory CD4 (IFN-γ+, IL-17+, TNF+) and CD8 (IFNγ+, TNF+) T cells in the brain and spinal cord Of the SOCS2-/- mice. However, following disease progression in SOCS2-/- mice, it was observed that in the remission phase they were unable to recover from the clinical signs caused by the demyelination process and CNS damage during the acute phase. Given the double response observed by SOCS2 during the development of the disease, it is inferred that SOCS2 is important for boosting the onset and onset of the acute phase, but it plays a key role in the recovery of locomotor deficiency, in addition to controlling the CNS lesions during EAE.